CORRELATION OF CRITICAL THINKING ABILITY TO DESCRIPTIVE WRITING SKILLS IN INDONESIAN LANGUAGE SUBJECT CLASS V - Roviani, Wulan Sri (Jurnal Kajian Pembelajaran dan Keilmuan, 2025)
This study aims to find out the ability to think critically, descriptive writing skills, and the relationship between the two in grade V students of SD Negeri 12 Sungai Kunyit. The type of research used is quantitative research with a correlational method. The research sample amounted to 30 students who were selected in total sampling. The research instruments are in the form of a critical thinking test and a descriptive writing test. Data analysis was carried out by descriptive test and Pearson correlation test with the help of SPSS. The results showed that the average score of students' critical thinking ability was 72.40 with a standard deviation of 13,372, while the average score of descriptive writing skills was 68.90 with a standard deviation of 13,762. The normality test showed a significance value of > 0.05, so that the data of the two variables were distributed normally. Pearson's correlation analysis showed a coefficient value of 0.983 with a significance of 0.000, which means that there is a very strong and significant positive relationship between critical thinking skills and descriptive writing skills. Thus, it can be concluded that the higher the student's critical thinking ability, the higher descriptive writing skills they have. This research provides the implication that the development of writing skills needs to be integrated with learning strategies that foster students' critical thinking skills.